Identification and characterisation of differentially expressed sequence tags in trypanosoma brucei brucei: molecular cloning ,expression and analysis of ADP-ribsylation factor 1 from African trypanosomes. - Osanya, A.O. (Brunel University, 1999)
African trypanosomes are extracellular flagellate haemoprotozoan parasites responsible for human sleeping sickness and related diseases in livestock. During their life cycle these parasites undergo morphological and physiological changes that require activation and repression of genes controlling their differentiation and development. To understand the molecular processes involved in trypanosome differentiation and development it is important to identify and examine genes and their products involved in these processes. Such genes and their products could reveal target molecules for intervention and control of trypanosomosis. The differential display RADES-PCR method was utilised to facilitate rapid identification of developmentally regulated sequences in the different life-cycle stages of Trypanosoma brucei brucei. Differential hybridisation using total cDNA probes and Northern blot analyses were used to verify stage-regulation of expression of transcripts that were differentially amplified. The cloned products were subjected to single-pass sequencing and analysed for homologues against the sequence databases by BLAST software. A total of 84 sequences had significant similarities to sequences already in the public databases; 72 expressed sequence tags (ESTs) matched non-T bruce; database entries and 12 sequences matched known T bruce; sequences. The remaining 117 sequences (58%) had no significant matches, but 62 (53%) of these contain motifs of recognisable proteins. A number of the differentially ESTs encode homologues of proteins involved in various functions such as cell division, DNA repair and replication, protein synthesis, metabolism, structural integrity, cellular signalling and trafficking. Several ESTs encode homologues of the adenosine diphosphate (ADP) ribosylation factor. ADP-ribosylation factors (ARFs) are small GTP-binding proteins of the ras-superfamily. ARFs have been shown to be essential in vesicle formation, intracellular and membrane trafficking and signal transduction. Such processes are probably involved in the co-ordination of complex parasite-host and/or parasite-parasite interactions and the regulation of growth and differentiation of the trypanosomes in response to external signals. To gain an insight into the molecular mechanisms involved in membrane trafficking, such as endocytosis and exocytosis, and on cell signalling in trypanosomes cloning and characterising of the ARF 1 gene was carried out. Full-length cDNA encoding the ARFI protein homologue of T b. bruce; was isolated and its nucleotide sequence determined. The T b. bruce; ARFI exhibited 92% identity with Plasmodium falciparum ARF1, 90% with human and bovine ARFI and 89% with yeast ARFI. The protein contained all the amino acid residues that are conserved in the GTP-binding domains for ARFI as well as those of the ras-superfamily. Similarly, clones of ARFI gene of T congolense and the 3' region of the T vivax gene were isolated and their nucleotide sequences determined. The GTP-binding domains of the encoded proteins are identical and conserved in the different trypanosome species. Southern blot analyses revealed that the ARFI gene occurs in a single copy in the parasite genome. Northern blot analyses revealed that the trypanosome ARF 1 gene is developmentally regulated; it is much more abundant in bloodstream forms of the parasite, but specifically in longer slender forms in T brucei. The complete open reading frame (ORF) was cloned in a bacterial expression vector and the protein purified to homogeneity. Recombinant T bruce; ARFI bound radio labelled GTP. Both GTP and GDP were very efficient competitors of [a32P]_GTP binding to the recombinant T bruce; ARFI protein. Western blot analyses revealed that the recombinant ARFI protein is recognised by sera from trypanosome-infected cattle. Polyclonal antibodies raised against the recombinant T bruce; ARFI protein revealed a single 21-22 kDa band in T b.' bruce; and T congolense lysa